Domesticity and the Female Demon in Charlotte Dacre’s Zofloya and Emily Brontë’s Wuthering Heights - Beauvais, Jennifer (Romanticism on the Net, 2006)
AbstractThis essay explores the transformations of the female demon in Dacre’s Zofloya and Brontë’s Wuthering Heights in relation to issues of femininity and domestic space. The mutability of the Gothic genre allows for the emergence of a new female demon introduced by Dacre and rewritten by Brontë. Tracing the domestication of Victoria and Catherine reveals the significance of the role of performance in the female demon’s acceptance into this feminized space. Masculinity and sensibility are also examined since the female demon is guided into the domestic sphere by effeminate male characters and then fall prey to their more masculine demon lovers. This essay argues that although the female demon’s newly acquired skill of performance and transformation allows her to explore the realm of the domestic, Dacre and Brontë suggest, by ultimately reverting to traditional Gothic perceptions of femininity, that her domestication is her demise.